The Effect of Interactive Content and Gamification on the Learning Rate and Motivation of Students in the Pediatric Nursing Virtual Internship Course - Mahboobeh Jamali; Seyed Hamid Seyed Bagheri; Lida Abazari; Aida Abazari; Mohammad Pordavar; Tabandeh Sadeghi (مجله دانشگاه علوم پزشکی جیرفت, 2024)
Introduction: The learning styles of students have changed in today's world and they need new teaching methods. In a situation like the spread of the Coronavirus, the use of virtual training such as gamification has flourished. Therefore, this study was conducted with the aim of investigating the effect of interactive content and gamification on the level of learning and students' motivation in the integrated course of pediatric nursing virtual internship. Materials and Methods: This semi-experimental study was conducted on 49 sixth-semester nursing students of Rafsanjan University of Medical Sciences. The level of students' learning was assessed using a researcher-made questionnaire before and 10 days after the intervention. The motivation level was measured after the intervention by the standard educational materials motivational questionnaire (IMMS). This practical unit encompassed a 10-day internship in pediatric nursing. Each group received practical training and virtual assignments for 5 days, which simultaneously covered other internship days, in the pediatric department . Data were analyzed using SPSS version 18 software. Results: Based on the results, there was a statistically significant difference between the students' average learning scores before and after the implementation of gamification. The average post-test scores were higher than the pre-test scores, with a significant difference (p < 0.05). The average scores and standard deviation of the sum of the standard motivational questionnaire components were108±13 after the intervention; which indicates a moderate level of motivation created by this intervention. Conclusion: The results of the present study indicated the positive effect of gamification on students' motivation and learning. Therefore, it is recommended to use this method to facilitate students' learning.